2017
DOI: 10.3389/fpls.2016.02037
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Characterization of Segregation Distortion Loci on Cotton Chromosome 18

Abstract: Segregation distortion is commonly detected via genetic mapping and this phenomenon has been reported in many species. However, the genetic causes of the segregation distortion regions in a majority of species are still unclear. To genetically dissect the SD on chromosome 18 in cotton, eight reciprocal backcross populations and two F2 populations were developed. Eleven segregation distortion loci (SDL) were detected in these ten populations. Comparative analyses among populations revealed that SDL18.1 and SDL1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 58 publications
6
30
0
Order By: Relevance
“…Segregation distortion (SD) is a general phenomenon in plants, but the percentage, degree and genetic effects may vary significantly across species (Dai et al 2016;Zhou et al 2015;Taylor and Ingvarsson 2003). In maize, it has been reported that 18 chromosome regions on 10 chromosomes were associated with SD (Lu, Romero-Severson, and Bernardo 2002) while 14 SD regions were reported for barley (Li et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Segregation distortion (SD) is a general phenomenon in plants, but the percentage, degree and genetic effects may vary significantly across species (Dai et al 2016;Zhou et al 2015;Taylor and Ingvarsson 2003). In maize, it has been reported that 18 chromosome regions on 10 chromosomes were associated with SD (Lu, Romero-Severson, and Bernardo 2002) while 14 SD regions were reported for barley (Li et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Markers showing distortion have been recorded in a number of crops 90,91 . Markers displaying SD can be useful in QTL mapping 92 as they are often linked to candidate genes for specific traits.…”
Section: Crossover Frequency and Recombination Varied Between Maps Dmentioning
confidence: 99%
“…For instance, it was found that regions of SD in sweet cherry, where 8% of markers showed distortion, are linked with hotspots containing fruit and bloom time traits, as well as a self-incompatibility modifier locus 93 . In cotton, several important agronomic traits have been recorded on chromosome 18 where 34% of markers showed distortion 90 .…”
Section: Crossover Frequency and Recombination Varied Between Maps Dmentioning
confidence: 99%
“…In an F2 population originating from a biparental cross, the expected ratio of genotypes AA:AB:BB (progeny homozygous for the allele from the first parent, heterozygotes and progeny homozygous for the allele from the second parent) in absence of segregation distortion is 1:2:1. Segregation distortion is observed across a wide range of taxa, including animals such as Drosophila [1,2] and mice [3], as well as crop species, including cotton [4], maize [5,6], potato [7], chickpea [8], barley [9] and wheat [10][11][12]. The primary explanation of the cause of segregation distortion is a selection pressure operating against one of the parental alleles at some stage of the development cycle, whether at meiosis through meiotic drive [1], through male gamete competition [4], or at the level of the zygote.…”
Section: Introductionmentioning
confidence: 99%
“…The diversity of criteria used in the literature reflect the difficulty of answering this question. Some authors settle for a simple chi-square test with the minimum significance threshold of p < 0.05 [5,10,[14][15][16], others report multiple significance thresholds [7,[17][18][19][20], whilst others use corrections for multiple testing, including false discovery rate (FDR) [11,12,21] and the even stricter Bonferroni correction [4,22]. This inconsistency has the further implication that many of the studies on segregation distortion are not comparable, which is problematic for the general advancement of our knowledge of segregation distortion.…”
Section: Introductionmentioning
confidence: 99%